Evaluasi Kepatuhan Pelaksanaan Surgical Safety Checklist Pada Tahap Time Out Di Rsi Siti Hajar Mataram - Nurul Aini; Elsye Maria Rosa (Malahayati Nursing Journal, 2026)
ABSTRACT The implementation of the Surgical Safety Checklist (SSC) at the time out stage is a critical component of patient safety systems in operating rooms, particularly in hospitals with a high volume of surgical procedures. This study aimed to evaluate the level of compliance with Surgical Safety Checklist (SSC) implementation at the time out stage in the Central Operating Theatre of RSI Siti Hajar Mataram. The study employed a descriptive quantitative design with an observational approach involving 250 surgical procedures conducted from January to March 2026. Data were collected through non-participant observation using a standardized Surgical Safety Checklist (SSC) checklist developed by the World Health Organization (2009), consisting of 10 indicators. Data analysis was conducted descriptively using percentage distribution to illustrate the compliance level for each indicator. The results showed that the compliance level of Surgical Safety Checklist (SSC) implementation at the time out stage was categorized as very high, with most indicators achieving compliance rates above 94%. Patient identity confirmation and surgical procedure confirmation reached 100% compliance, indicating optimal and consistent implementation. Other indicators, including surgical site confirmation, site marking, team introduction, anesthesia risk anticipation, bleeding risk anticipation, equipment readiness, imaging readiness, and team readiness before incision, were also categorized as very good. The lowest compliance was observed in imaging readiness and team introduction, indicating the need for improved consistency, particularly in coordination and supporting documentation readiness. Overall, the implementation of Surgical Safety Checklist (SSC) at the time out stage has been carried out in accordance with international standards; however, strengthening team communication and integration of supporting services remains necessary to further enhance patient safety. Keywords: Surgical Safety Checklist, Time Out, Compliance, Patient Safety, Hospital Management. ABSTRAK Pelaksanaan Surgical Safety Checklist (SSC) pada tahap time out merupakan komponen penting dalam sistem keselamatan pasien di ruang operasi, khususnya pada rumah sakit dengan volume tindakan pembedahan yang tinggi. Penelitian ini bertujuan untuk mengevaluasi tingkat kepatuhan pelaksanaan SSC pada tahap time out di Instalasi Bedah Sentral RSI Siti Hajar Mataram. Penelitian menggunakan desain deskriptif kuantitatif dengan pendekatan observasional terhadap 250 tindakan operasi selama periode Januari–Maret 2026. Pengumpulan data dilakukan melalui observasi non-partisipatif menggunakan instrumen checklist Surgical Safety Checklist (SSC) standar World Health Organization (2009) yang terdiri dari 10 indikator. Analisis data dilakukan secara deskriptif dalam bentuk persentase untuk menggambarkan tingkat kepatuhan pada setiap indikator. Hasil penelitian menunjukkan bahwa tingkat kepatuhan pelaksanaan Surgical Safety Checklist (SSC) pada tahap time out berada pada kategori sangat tinggi dengan capaian di atas 94% pada hampir seluruh indikator. Komponen konfirmasi identitas pasien dan konfirmasi prosedur operasi mencapai kepatuhan 100%, sementara indikator lainnya seperti konfirmasi lokasi operasi, penandaan lokasi, perkenalan tim, antisipasi risiko anestesi, antisipasi perdarahan, kelengkapan alat, kesiapan imaging, dan kesiapan tim sebelum insisi juga menunjukkan kategori sangat baik. Indikator dengan kepatuhan relatif lebih rendah terdapat pada kesiapan imaging dan perkenalan tim, yang mengindikasikan perlunya peningkatan konsistensi pada aspek koordinasi dan kesiapan penunjang. Temuan ini menunjukkan bahwa implementasi Surgical Safety Checklist (SSC) tahap time out telah berjalan sesuai standar internasional, namun penguatan pada aspek komunikasi tim dan integrasi layanan penunjang masih diperlukan untuk meningkatkan keselamatan pasien secara berkelanjutan. Kata Kunci: Surgical Safety Checklist, Time Out, Kepatuhan, Keselamatan Pasien, Manajemen Rumah Sakit.